Effect of Feeding Frequency on Feed Utilization Efficiency and Growth of Asian seabass (Lates calcarifer) Fingerlings - Dhea Mayang Saputri; Seto Windarto; Diana Chilmawati (Journal of Aquaculture and Fish Health, 2025)
Asian seabass (Lates calcarifer) is an economically important euryhaline fish. Feed absorbs 60–70% of the total production costs; therefore, regulating feeding frequency is necessary to increase feed utilization efficiency. Feeding frequency is the amount of feed given to fish daily. This study aimed to examine the effects of feeding frequency on the utilization of a phytase enzyme in the feed of Asian seabass fingerlings. The experimental fish used were Asian seabass fingerlings (7.57±0.28 cm in length and 5.31±0.15 g in weight) with a stocking density of one fish/L. This research used an experimental method with a completely randomized design (CRD), which consisted of four treatments and three replicates. The treatments were feeding frequencies of 1 (A), 2 (B), 3 (C), and 4 (D) times a day with the addition of 0.1 g/kg feed of the phytase enzyme. The feeding method used was the relative feeding rate, and the feed dose was 6% of the fish biomass. The results showed that feeding frequency significantly affected total feed consumption (TFC), feed conversion ratio (FCR), feed utilization efficiency (FUE), protein efficiency ratio (PER), and relative growth rate (RGR). However, they had no significant effect on the survival rate (SR) of Asian seabass fingerlings. Treatment C (3 times a day) showed the highest TFC, FCR, FUE, PER, and RGR, which were 251.85±1.61 g, 1.45±0.03, 69.08±1.50%, 1.51±0.03, and 3.90±0.11%/day, respectively. The water quality in the study area was suitable for Asian seabass cultivation. This study concluded that feeding three times a day resulted in the best FUE and RGR of Asian seabass fingerlings.